Care for patients with hypersensitivity to Hymenoptera venom challenge for therapeutic team - Kuriata-Kempska, Krystyna; Krzemińska, Sylwia; Borodzicz, Adriana; Arendarczyk, Marta (Journal of Education, Health and Sport, 2017)
This insect venom allergy is a special form of allergy because it carries a high risk of developing Anaphylaxis, the most severe, life-threatening form of allergic reaction. This is one of the most dangerous allergies. It is a major problem in modern allergy because it is still under-diagnosed in its pathomechanism, diagnosis and treatment. In the care of this group of patients, it is important to treat, educate patients, teach them the Principles of prevention, use drugs for immediate intervention, and most of all, the adrenaline. These tasks should cover all staff Responsible for the care of the patient both physicians, psychologists and nurses.